Biochemical bone turnover markers : significance in patients with osteoporosis - Mihaljević, Ivan, liječnik (Array, 2009)
Summary: Osteoporosis is a systemic disease, which is characterized by reduced bone mass and microarchitectural deterioration of the bone tissue, resulting in an increased risk of fracture. Since osteoporosis is today a disease with high incidence rate, the aim of this study was to determine a correlation between bone mass density (BMD) and concentration of biochemical bone turnover markers – deoxypyridinoline (DPD) as a marker of bone resorption, and osteocalcin (OC) as a marker of bone formation. The study included 70 women between 33 and 76 years of age. In all women BMD was measured by Dual X-ray Absorptiometry (DXA) as a T-score. T-score was defined as the number of standard deviations of the bone mass density from the maximum bone mass density in young adults. According to T-score, patients were divided into three groups: patients with osteoporosis, patients with osteopenia and control group consisting of patients with normal T-score. DPD in urine and OC in serum were measured by a routine procedure. Results: a negative correlation between BMD and concentration of bone turnover marker was discovered. One-way analysis of variance and Pearson correlation were used for statistical analysis, with a P value <0.05 being considered significant. Although a negative correlation was discovered, we concluded that both procedures have a significant role in diagnosis and follow-up of patients with osteoporosis